10.04: Behaviour of plane frames of high strength steel in fire. (13th September 2017) - Shakil, Saani; Lu, Wei; Puttonen, Jari
ABSTRACT: Mechanical properties given in the design code EN 1993‐1‐2, are obtained from researches on low strength mild steel. The applicability of these material properties to high strength steel (HSS) grade is thus, an area of interest. In this study, the behaviour of a planar frame made of high strength steel (HSS) in fire is studied by applying the finite element method. A material model was created using stress‐strain formulation from EN 1993‐1‐2 with reduction factors being from elevated temperature tests of HSS in literature as well as from EN 1993‐1‐2. FE analysis is carried out by Abaqus software using dynamic explicit solver so that non‐linear deformations can be simulated. Continuum elements are used to create FE model because of their capabilities to catch temperature distribution and local failure across cross‐sections of frame members. The FE model is validated by simulating experimental tests on mild steel frame from literature. With this validated model, the behaviour of the frames made of mild steel or HSS were compared based on deformation, critical temperatures, duration for collapse, and failure modes. Further, the behaviour of HSS frames using material data from different references were also compared. It is observed that deviations of mechanical properties at elevated temperatures from those in EN 1993‐1‐2 affect the behaviour of the frame.